Lipopolysaccharides and trophic factors regulate the LPS receptor complex in nodose and trigeminal neurons - Kunda, Patricia Elena (2014)
Binding of bacterial lipopolysaccharides (LPS) to toll-like receptor 4 (TLR4) triggers an innate immunoresponse associated with pain and inflammation. The expression, and to a greater extent the regulation of TLR4 and its auxiliary proteins (myeloid differentiation protein 1 (MD1), myeloid differentiation protein 2 (MD2) and cluster of differentiation 14 (CD14)), are both poorly understood in trigeminal and nodose neurons. We used a combination of Western blotting, semi-quantitative polymerase chain reaction (PCR), pharmacological manipulation and immunohistochemistry. The expression pattern and regulation by LPS and trophic factors of TLR4/MD2/CD14 and radioprotective protein of 105 kDa (RP105)/MD1 were determined in neonatal trigeminal and nodose mice neurons. We found that all these proteins were expressed in both trigeminal and nodose neurons. The trophic factors Artemin and nerve growth factor (NGF) up-regulated MD2 and RP105 mRNA levels in trigeminal neurons. In nodose neurons the trophic factors brain-derived neurotrophic factor (BDNF), ciliary neurotrophic factor (CNTF) and leukemia inhibitory factor (LIF) up-regulated MD1 and RP105 mRNA levels. Also we observed that in both neuronal types LPS acutely (within 20 min) down-regulated CD14 and MD2 mRNAs. In addition, LPS increased significantly the proportion of trigeminal and nodose neurons expressing nociceptin/orphanin FQ in culture probably acting via TLR4/MD2. Although the exact mechanisms underlying the regulation by trophic factors and LPS require further elucidation, the findings of this study indicate that LPS acts through its archetypical receptor in trigeminal and nodose neurons.